2015
DOI: 10.1177/0194599815572123
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Costs for ED Visits after Pediatric Adenotonsillectomy

Abstract: A significant portion of children present to the ED after T&A for poorly controlled pain, dehydration, or fever. The costs from these visits are significant. Accounting for these costs in the global care for pediatric T&A could assist in calculating appropriate reimbursement for bundled payments in this climate of health care reform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 17 publications
(30 reference statements)
1
65
2
1
Order By: Relevance
“…16 American data report a combined bleed rate of 3.3%. 17 In day-stay patients 14 of 18 primary bleeds, both minor and major, occurred outside the standard 4-hour observation window (0.4% of all day-stay patients). That there were no adverse outcomes in this group is testament to the reliability of the daystay selection criteria, which allowed these patients to return quickly for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 American data report a combined bleed rate of 3.3%. 17 In day-stay patients 14 of 18 primary bleeds, both minor and major, occurred outside the standard 4-hour observation window (0.4% of all day-stay patients). That there were no adverse outcomes in this group is testament to the reliability of the daystay selection criteria, which allowed these patients to return quickly for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The representation with postoperative pain rate of 1.3% is below the 2% found in other series. 17 A number of children with repeat presentations to the emergency department after tonsillectomy ultimately resulted in a posttonsillectomy bleed. Almost a quarter of patients who returned with PONV went on to develop a posttonsillectomy bleed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this single-digit percentage, it is evident that CT imaging must be promptly available for severely injured children. CT is the quickest and most exact imaging modality in emergent situations requiring quick and have previously found that a significant portion of children present to the ED after adenotonsillectomy for poorly controlled pain, dehydration, or fever which is associated with significant costs [8]. The predominant ENT presentations among the paediatric population in this study were more or less complex in nature, and this highlights the demand for prompt disposition of ENT subspecialist support.…”
Section: Age and Gendermentioning
confidence: 69%
“…Of the remainder, the commonest presenting problems featured abdominal pain (16.3%), self-harm (10.6%), fits, faints and funny turns (10.4%), breathing difficulty (7.2%), and intoxication (6.0%) [2]. Other authors have reviewed subgroups of patients limited to medical [1] or surgical problems or issues related to one subspecialty only [6][7][8][9][10]. In Switzerland, PEM has only been officially recognised as a subspeciality by the Foederatio Medicorum Helveticorum (FMH, Swiss Medical Association) since January 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers share actual internal costs, but the costing method and degree of health service coverage vary. Intermountain Healthcare investigators have published studies using data from an activity- based cost accounting system, but it only contains hospital costs [21, 22]. Filice et al [23] used internal costs from a Department of Veterans Affairs cost accounting system, but the department does not share the confidentiality concerns of nongovernment providers.…”
Section: Discussionmentioning
confidence: 99%